2011
DOI: 10.1021/ma102394s
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Relaxation of Hydrophilic Poly(vinylpyrrolidone) in Chloroform Studied by Broadband Dielectric Spectroscopy

Abstract: Dielectric relaxation caused by the segmental motion of poly(vinylpyrrolidone) (PVP) was studied in chloroform solutions with 5−40 wt % PVP at temperatures between 298 and 210 K above the melting temperature of chloroform (210 K) to obtain information on the dynamics of hydrophilic polymer. The asymmetric broadening of the loss peak and the fragility, i.e., the degree of deviation from the Arrhenius temperature dependence of relaxation time, increase with increasing PVP concentration. Both are due to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 40 publications
1
34
1
4
Order By: Relevance
“…For PVP solutions with polar solvents, two relaxation processes have been observed at frequencies above 100 MHz and below 10 MHz at 298 K. 38,38,39,45,46 The origin of these relaxation processes has been determined to be the segmental motion of PVP for the process at frequencies below 10…”
Section: Molecular Origin Of the Relaxation Processesmentioning
confidence: 99%
“…For PVP solutions with polar solvents, two relaxation processes have been observed at frequencies above 100 MHz and below 10 MHz at 298 K. 38,38,39,45,46 The origin of these relaxation processes has been determined to be the segmental motion of PVP for the process at frequencies below 10…”
Section: Molecular Origin Of the Relaxation Processesmentioning
confidence: 99%
“…The loss peak at 100 Hz is partly concealed by ionic contributions, namely, EP and dc conductivity. We also studied the two dielectric relaxation processes at 298 K in PVP solutions with water, alcohol, and chloroform and examined the origins in detail [3,[46][47][48][49]. The relaxation process observed above 100 MHz is the primary relaxation of the solvents.…”
Section: Figurementioning
confidence: 99%
“…In addition to the studies at 298 K, we studied the dielectric constant of PVP solutions with chloroform and PG from the liquid state to the glassy state over a wide range of temperatures and frequencies [48,50]. In these studies, the PVP-process observed at 298 K was the α-relaxation of PVP in solution, which is related to the glass transition of the solutions.…”
Section: Figurementioning
confidence: 99%
“…This indicates that the relaxation time of alcohols is determined by ρ HB , the density of hydrogen-bonding sites in solution, which changes with increasing PVP concentration. Moreover, PVP solutions of chloroform, which has a lower permittivity than alcohol, are used to observe the PVP relaxation at different PVP concentrations and temperatures [17]. The results indicated that the apparent activation energy increases with decreasing temperature, which is known as the Vogel-FulcherTammann-Hesse (VFTH) [18][19][20] temperature dependence of relaxation time.…”
Section: Dielectric Relaxation Of Hydrophilic Polymer In Solutionsmentioning
confidence: 99%